Age and HIV stage at initiation of highly active antiretroviral therapy determine non-reversal of stunting at 3 years of treatment - Putu Diah Vedaswari; Ketut Dewi Kumara Wati; I Gusti Lanang Sidiartha; I Gusti Ayu Putu Eka Pratiwi; Hendra Santoso; Komang Ayu Witarini (Indonesian Pediatric Society, 2018)
Background Highly active antiretroviral therapy (HAART) has been reported to improve growth, especially in the first 2 years of treatment. It is not clear whether catch up growth is maintained after 2 years of HAART. Objective To assess growth in stunted children with HIV after 3 years of HAART and analyze possible risk factors for non-reversal of stunting. Methods This study was done from May 2016 to April 2017 to follow children with HIV who started HAART between January 2009 and April 2014, and continued for 3 years. Inclusion criteria were children with HIV, aged < 18 years, compliance to the regimen, and stunting. Exclusion criteria were patients lost to follow up or who died prior to 3 years of HAART. Non-reversal of stunting was defined as HAZ â‰¤ -2SD after 3 years of HAART. Possible risk factors for non-reversal were analyzed using Chi-square test with P<0.05, as well as risk ratio (RR) and 95% confidence intervals (CI). Results Of 150 HIV-infected pediatric patients, 115 were on HAART and 55 (47.8%) were stunted at HAART initiation. Of the 55 stunted and HAART-treated children, 31 (56.4%) were male. Baseline median age was 3.6 years (interquartile range 0.37-8.48). Non-reversal occurred in 32 (58.2%) subjects. Multivariate Cox regression model analysis showed predictors of non-reversal after 3 years of HAART to be age >2 years (RR 16.05; 95%CI 2.89 to 89.02; P=0.002) and HIV stage III-IV (RR 8.93; 95%CI 1.47 to 54.37; P=0.017). Conclusion HAART initiation at age >2 years and HIV clinical stage III-IV at diagnosis are risk factors for non-reversal of stunting after 3 years of HAART.